Chemokine Receptor CCR1 Regulates Inflammatory Cell Infiltration after Renal Ischemia-Reperfusion Injury - Furuichi, Kengo (2008)
Neutrophils and macrophages rapidly infiltrate the kidney after renal ischemia-reperfusion injury, however specific molecular recruitment mechanisms have not been fully delineated for these cell types. Here we provide genetic and pharmacologic evidence supporting a positive role for the chemokine receptor CCR1 in macrophage and neutrophil infiltration in a 7 day mouse model of renal ischemia-reperfusion injury. By day 7, injured kidneys from mice lacking CCR1 contained 35% fewer neutrophils and 45% fewer macrophages than injured kidneys from wild type control mice. Pretreatment of WT mice with the specific CCR1 antagonist BX471 also suppressed neutrophil and macrophage infiltration in the model. Injured kidneys from mice lacking CCR1 also had reduced content of the CCR1 ligands CCL3 (MIP-1α) and CCL5 (RANTES) compared to injured kidneys from wild type controls, suggesting a leukocyte source for these inflammatory chemokines and existence of a CCR1-dependent positive feedback loop for leukocyte infiltration in the model. Local leukocyte proliferation and apoptosis were detected after injury, but were not dependent on CCR1. Also, the extent of necrotic and fibrotic damage and decline in renal function in injured kidneys was similar in wild type and CCR1-deficient mice. Thus, CCR1 appears to regulate trafficking of macrophages and neutrophils to kidney in a mouse model of renal ischemia-reperfusion injury, however this activity does not appear to affect tissue injury.